2021
DOI: 10.3389/fphys.2021.668144
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity, Ventilatory Response, and Gas Exchange in COPD Patients With Mild to Severe Obstruction Residing at High Altitude

Abstract: BackgroundExercise intolerance, desaturation, and dyspnea are common features in patients with chronic obstructive pulmonary disease (COPD). At altitude, the barometric pressure (BP) decreases, and therefore the inspired oxygen pressure and the partial pressure of arterial oxygen (PaO2) also decrease in healthy subjects and even more in patients with COPD. Most of the studies evaluating ventilation and arterial blood gas (ABG) during exercise in COPD patients have been conducted at sea level and in small popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
1
5
0
2
Order By: Relevance
“…It seems one night of acclimatization improved CRF but did not yet have a significant impact on the oxygen saturation. Another study done in high-altitude natives suffering from COPD and a healthy control group at 2640 m showed a lower exercise capacity of COPD patients and the exercise capacity worsening with more severe COPD [119]. In this study a statistically significant lower arterial oxygen saturation was noted in the COPD patients than in the healthy control.…”
Section: Effects Of Pre-existing Respiratory Diseasessupporting
confidence: 48%
“…It seems one night of acclimatization improved CRF but did not yet have a significant impact on the oxygen saturation. Another study done in high-altitude natives suffering from COPD and a healthy control group at 2640 m showed a lower exercise capacity of COPD patients and the exercise capacity worsening with more severe COPD [119]. In this study a statistically significant lower arterial oxygen saturation was noted in the COPD patients than in the healthy control.…”
Section: Effects Of Pre-existing Respiratory Diseasessupporting
confidence: 48%
“… 8 In Bogotá, a city located at high altitude (2640 m, BP: 560 mmHg), the PaCO 2 at rest in healthy subjects is around 33 mmHg and the PaO 2 65 mmHg, with values lower than 60 mmHg in elderly 9 and even lower in COPD patients. 10 , 11 In a previous study in COPD patients residing in Bogotá, we demonstrated a high prevalence of PH, particularly in patients with less severe airflow obstruction. 12 Although there are several pathophysiological mechanisms related to the development of PH, probably the alveolar hypoxia at high altitude is a fundamental factor to promote and develop PH in these patients.…”
Section: Introductionmentioning
confidence: 73%
“…Unlike similar studies at sea level, the degree of hypoxemia both at rest and during exercise in all degrees of COPD severity was higher, and due to adaptation mechanisms to altitude, there were changes in the ventilatory pattern with lower PaCO 2 values and higher ventilatory equivalents (VE/VCO 2 ). 11 Considering the coexistence of pathophysiological mechanisms related to both pulmonary vascular compromise and COPD, it is expected that the ventilatory and gas exchange alterations during exercise that we have described in patients with COPD residing at high altitude will be more severe in those patients with associated PH.…”
Section: Introductionmentioning
confidence: 89%
“…Exercise-induced arterial hypoxemia influences the decline of O 2max in mild hypoxia [ 32 , 33 ]. Additionally, greater arterial desaturation and lower O 2peak were reportedly observed in chronic obstructive pulmonary disease patients compared with those in healthy populations [ 34 ], suggesting a relation between arterial desaturation and aerobic capacity in healthy and diseases populations. The absence of a correlation between ΔSaO 2 and Δ O 2peak at 21–12% O 2 in this study suggests elevated HR can compensate arterial desaturation (Fig.…”
Section: Discussionmentioning
confidence: 99%